2019
DOI: 10.5539/jas.v11n6p160
|View full text |Cite
|
Sign up to set email alerts
|

Water, Soil and Nutrients Losses by Runoff at Hillslope Scale in Agricultural and Pasture Production in Southern Brazil

Abstract: Agricultural activity, if not well managed, is an important source of water pollution mainly by surface runoff. The aim of this study was to evaluate losses of water, soil and soluble nutrient (phosphorus, nitrogen and carbon) via runoff in large plots (hillslope from 3,000 to 11,000 m2) at slope of 4 to 5% in annual crops (corn and sunflower) and pasture systems under no-tillage and no-pesticides. The study was carried out at the Canguiri Experimental Farm of the Federal University of Paraná, South… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…This soils were associated with lower levels of soil organic carbon, evidencing the importance of carbon inputs from roots into the soil. Coblinski et al (2019) studied the same experimental area, and showed that soil bulk density, porosity, soil water availability, as well SOC influence soil structural quality. According to Colombi et al (2018), interactions between root architecture, plant water uptake, soil moisture, and soil penetration resistance are little studied.…”
Section: Relationships Between Soil Structure Root Properties and Soi...mentioning
confidence: 99%
“…This soils were associated with lower levels of soil organic carbon, evidencing the importance of carbon inputs from roots into the soil. Coblinski et al (2019) studied the same experimental area, and showed that soil bulk density, porosity, soil water availability, as well SOC influence soil structural quality. According to Colombi et al (2018), interactions between root architecture, plant water uptake, soil moisture, and soil penetration resistance are little studied.…”
Section: Relationships Between Soil Structure Root Properties and Soi...mentioning
confidence: 99%
“…Surface runoff in hillslope soils has significant impacts on sediment yield, nutrient transport, and consequently water quality [8,9]. In vineyards, heavy rainfall often increases and accelerates several negative impacts, including soil aggregate breakdown, soil sealing, nutrient leaching, excessive vine vegetative growth, and fruit disease [10].…”
Section: Introductionmentioning
confidence: 99%
“…Most studies of water, sediment and nutrient losses in Brazil with soil tillage and management systems have been done in small plots with simulated or natural rainfall (Bertol et al, 2011; Bertol, Rizzi, Bertol, & Roloff, 2007; Denardin, Kochhann, Faganello, Sattler, & Manhago, 2008; Gebler, Bertol, Ramos, Louzada, & Miquelluti, 2012; Guadagnin, Bertol, Cassol, & Amaral, 2005; Silva & De Maria, 2011). Studies at greater scale are needed and field experiments with large plots in Brazil have been increased recently (Coblinski et al, 2019; Deuschle et al, 2019; Londero et al, 2018; Merten et al, 2015; Ramos et al, 2014). Losses of soil, water and agrochemicals in a watershed cannot be estimated by the sum of results from individual fields, even from large plots (Ding et al, 2016; Raclot et al, 2009; van de Giesen, Stomph, & de Ridder, 2005) so studies at watershed scale following the real field condition are essential to assess water quality (Capoane, Tiecher, Schaefer, Ciotti, & dos Santos, 2015; Gafur, Jensen, Borggaard, & Petersen, 2003; Martínez‐Casasnovas, Ramos, & Benites, 2016; Niu et al, 2015; Nu‐Fang, Zhi‐Hua, Lu, & Cheng, 2011; Shi et al, 2012; Shore et al, 2014; Shore et al, 2017) as well as to calibrate empirical mathematical models (Durães, de Mello, & Naghettini, 2011; Raclot et al, 2009; Shi et al, 2012; Tong & Chen, 2002; van de Giesen et al, 2005).…”
Section: Introductionmentioning
confidence: 99%